2002
DOI: 10.1046/j.1439-0264.2002.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Gross and Microscopic Observations on the Lingual Structure of the Florida Manatee Trichechus manatus latirostris

Abstract: The tongue of the Florida manatee (Trichechus manatus latirostris) was studied macroscopically, light and electron microscopically. The tongue was slender, muscular and firmly fixed in the oral cavity; only the cranial tip was free and mobile. Numerous filiform papillae were distributed over the dorsal surface of the rostral tongue. Multiple raised, round fungiform-like papillae were distributed over most of the dorsum. Typical fungiform papillae were restricted to the lateral margins of the tongue. Foliate pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 22 publications
3
26
1
Order By: Relevance
“…Samples from the middle and caudal third were examined histologically and salivary glands beneath the connective tissue layer were observed. This finding was also reported by Levin and Pfeiffer (2002) for the Amazonian manatee (Trichechus inunguis).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Samples from the middle and caudal third were examined histologically and salivary glands beneath the connective tissue layer were observed. This finding was also reported by Levin and Pfeiffer (2002) for the Amazonian manatee (Trichechus inunguis).…”
Section: Discussionsupporting
confidence: 87%
“…It was covered by a keratinized stratified epithelium. Despite the tongue morphology of mammals being related to their life style, stratification and keratinization are basic and common characteristics of the tongue epithelium in most species of terrestrial (Benetti et al, 2009;Erdunchaolu et al, 2001;Silva, 1999;Watanabe et al, 1992) and aquatic mammals (Guimarães et al 2011;Levin and Pfeiffer, 2002;Yoshimura et al, 2002). Shimoda et al (1996) reported a nonkeratinized stratified epithelium in the tongue of Sea Otter (Enhydra lutris).…”
Section: Discussionmentioning
confidence: 99%
“…Similar structures were described in saru monkeys (Watanabe et al, 1992), camel (Erdunchaolu et al, 2001), Florida manatee (Levin and Pfeiffer, 2002), California sea lion (Yoshimura, 2002), three-toe sloth (Benetti et al, 2009) and squirrel monkey (Branco et al, 2011). Some animals reported by Guimarães (2006) presented non-keratinized stratified pavement epithelium different from the one found in this study.…”
Section: Discussionsupporting
confidence: 60%
“…In general, the literature reports that in the most primate species, the tongue is composed of three or four types of papillae: filiform, fungiform, vallate, and foliate (not always present in some species). Filiform papilla is the most common (Chamorro et al,1986; Chibugo,1993; Dyce et al,2010; Pfeifer et al,2000; Schwarze and Schröder,1970; Sisson and Grossman,1959), except for the manatee, which has only a small taste of these clusters at the apex of the tongue (Levin,1999).…”
Section: Discussionmentioning
confidence: 99%